Knowledge and Attitudes Significantly Influence Consumption Behavior of the Free Nutritious Meals Program Among Students at High School - Indah Annisa Auliah; Alkhair Alkhair; M. Noris; Darmin Darmin (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
The Free Nutritious Meals Program is a governmental initiative designed to improve the nutritional status of school‑age children by providing daily nutritious meals. The effectiveness of this program depends not only on food availability but also on students’ knowledge and attitudes toward healthy eating behaviors. This study aims to analyze the influence of knowledge and attitudes on consumption behavior related to the Free Nutritious Meals Program among students at State Senior High School 3 in Bima City. A cross‑sectional design was employed involving a population of all students at the school, with a sample of 160 students selected through stratified random sampling. Data were collected using a structured questionnaire and analyzed using simple and multiple linear regression. A total of 124 students demonstrated insufficient knowledge, 102 students exhibited positive attitudes, and 119 students showed good consumption behavior related to the Free Nutritious Meals Program. Knowledge significantly influenced consumption behavior (p < 0.001), and attitude also had a significant effect (p < 0.001). When analyzed together, knowledge and attitude jointly influenced consumption behavior (p < 0.001). Attitude had a stronger effect (B = 1.103) compared to knowledge (B = 0.258). Both variables explained 27.0% of the variation in consumption behavior, while the remaining 73.0% was attributed to other factors not examined in this study. In conclusion, knowledge and attitude significantly influence students’ consumption behavior related to the Free Nutritious Meals Program at State Senior High School 3 in Bima City.Keywords: free nutritious meals; knowledge; attitudes; consumption behavior; high school students